MENINGKATKAN KINERJA KARYAWAN DI PERUSAHAAN MINYAK DAN GAS: PENINJAUAN DARI DISIPLIN KERJA, KNOWLEDGE SHARING DAN MOTIVASI KERJA - Anggraini, Resty; Susita, Dewi; Wolor, Christian Wiradendi (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
The aim of this research is to examine how work discipline and knowledge sharing affect employee performance with work discipline as a mediator. The research employs a quantitative method and is conducted through structural equation modeling analysis using AMOS. The respondents involved in this research are employees of PT Pertamina Patra Niaga at the central office, with a sample size of 355 employees selected through proportionate sampling method. The results show that work discipline, knowledge sharing, and motivation do not have a significant impact on employee performance. However, work discipline and knowledge sharing have a positive effect on work motivation. Finally, work discipline and knowledge sharing do not have a direct influence on employee performance but rather through work motivation mediation